Complex cases of acquired pulmonary vein stenosis after radiofrequency ablation: is surgical repair an option?. Issue 1 (12th February 2018) - Schoene, Katharina; Sommer, Philipp; Arya, Arash; Kostelka, Martin; Mohr, Friedrich W; Misfeld, Martin; Vollroth, Marcel; Bollmann, Andreas; Lurz, Julia; Hindricks, Gerhard; Seeburger, Joerg
Abstract: Aims: Results of catheter based interventional treatment for pulmonary vein stenosis (PVS) following radiofrequency ablation (RFA) for atrial fibrillation remain suboptimal. Surgical repair may represent an alternative therapy, though long-term results have not been thoroughly investigated. Methods and results: We retrospectively assessed all patients in our centre undergoing surgical repair for radiofrequency-induced PVS. Data regarding surgical technique, clinical outcome, and rate of pulmonary vein (PV) restenosis were collected and analysed. Between 2004 and 2016, the rate for PVS resulting from RFA for atrial fibrillation in our institution was 0.79% (76/9633). During this period, five male patients with multiple PVS (3 ± 1) underwent surgical repair of a total of 13 symptomatic PVS. Surgery was performed in a standard setting under cardiopulmonary bypass. Stenotic veins were incised longitudinally followed by a patch augmentation plasty using either bovine pericard ( n = 7) or polytetrafluoroethylene (PTFE) patches ( n = 5). Localization of incision was on the anterior side of the PV only ( n = 8) or on both the anterior and posterior sides ( n = 4). In one PVS lesion, mechanical dilatation was sufficient. Long-term follow-up after 60 ± 69 months revealed an average restenosis rate of 38%. Restenosis was defined as narrowing >70%. All patients reported clinical improvement of symptoms at follow-up. Conclusion: Even in the era of wide circumferential lesions, PVS still occurs. While surgical PV patch plasty represents a valuable treatment option, restenosis remains an issue during follow-up. Nevertheless, surgical repair achieves highly acceptable long-term results for RFA-acquired PVS. Hence, it should be routinely discussed as a therapeutic option in cases with multiple PVS.